Where God meets man : Luther's down-to-earth approach to the gospel - Forde, Gerhard O.
"The fundamental theme of the book is the "down-to-earth" character of Luther's theology in the hope that it will help individual Christians today to be both faithful to God and true to their human and social responsibilities. This 50th anniversary edition includes a preface by Marianna Forde and a new study guide by Bradley C. Jenson, created to encourage new readings and conversation about Gerhard O. Forde's influential take on Luther, theology, and the church."--back cover.